Integration of base64 encoding, vigenère cipher, and LSB steganography for securing learning materials in learning management systems. - Deden Pradeka; Deandy Zahran Vierdansyah; Devi Aprianti Rimadhani Agustini; Anugrah Adiwilaga; Syifa Aqila Humaira; Aidha Salsa Billa; Budiman (LPPMPK- Universitas Muhammadiyah Cileungsi, 2026)
The increasing use of Learning Management Systems (LMS) in digital education raises significant concerns regarding the confidentiality and integrity of learning materials stored and transmitted within the platform. This study proposes a layered security mechanism that integrates cryptography and steganography to protect educational files in an LMS environment. The system implements Base64 encoding for data transformation, Vigenère cipher encryption for key-based protection, Fisher–Yates shuffle for ciphertext randomization, and Least Significant Bit (LSB) steganography to conceal encrypted data within digital images. The proposed method was implemented in a PHP-based LMS prototype and evaluated using learning files in .ppt and .pdf formats as test objects. Encrypted files were embedded into high-resolution cover images with a resolution of 6000 × 4000 pixels. Experimental results show that the system successfully performs the complete processes of encryption, embedding, extraction, and decryption with a 100% integrity success rate, indicating that the original files can be perfectly reconstructed after extraction. Image quality analysis shows high visual imperceptibility with PSNR values above 60 dB and very low MSE values. However, the embedding process introduces storage overhead, resulting in an average file size increase. These results demonstrate that the proposed layered approach effectively enhances data confidentiality and concealment in LMS environments, although optimization of storage efficiency remains necessary for large-scale implementationThe increasing use of Learning Management Systems (LMS) in digital education raises significant concerns regarding the confidentiality and integrity of learning materials stored and transmitted within the platform. This study proposes a layered security mechanism that integrates cryptography and steganography to protect educational files in an LMS environment. The system implements Base64 encoding for data transformation, Vigenère cipher encryption for key-based protection, Fisher–Yates shuffle for ciphertext randomization, and Least Significant Bit (LSB) steganography to conceal encrypted data within digital images. The proposed method was implemented in a PHP-based LMS prototype and evaluated using learning files in .ppt and .pdf formats as test objects. Encrypted files were embedded into high-resolution cover images with a resolution of 6000 × 4000 pixels. Experimental results show that the system successfully performs the complete processes of encryption, embedding, extraction, and decryption with a 100% integrity success rate, indicating that the original files can be perfectly reconstructed after extraction. Image quality analysis shows high visual imperceptibility with PSNR values above 60 dB and very low MSE values. However, the embedding process introduces storage overhead, resulting in an average file size increase. These results demonstrate that the proposed layered approach effectively enhances data confidentiality and concealment in LMS environments, although optimization of storage efficiency remains necessary for large-scale implementation